Market’s Reaction and Covid-19 Pandemic - Willim, Andre Prasetya; Santoso, Hadi (Journal of Asian Multicultural Research for Economy and Management Study, 2022)
The corona virus (Covid-19) is causing global disruption. There is evidence from case studies that COVID-19 has had a substantial impact on the capital market. The present worldwide epidemic of COVID-19 has a detrimental effect on financial markets, including traditional stock markets and commodities markets. The goal of this research is to empirically assess the impact of COVID-19 on the functioning of the capital market by analyzing trading volume activity and average stock price movement. Descriptive statistical tests, normality tests, and Wilcoxon Signed Rank Test hypothesis testing were utilized to analyze the study data. The results of the research indicate that there is no significant difference in trading volume activity before and after the first case of COVID-19 was found in Indonesia and before and after the PSBB policy was announced to be implemented. In contrast, the study findings indicate that there are substantial changes in the average closing stock prices before and after the first case of COVID-19 was found in Indonesia and before and after the PSBB policy was implemented. Thus, the findings of this research show that information about the first instance of COVID-19 and the announcement of the adoption of the PSBB policy affect the capital market’s response to stock price fluctuations. This discovery is anticipated to give a contribution that may assist investors in adjusting to the execution of a superior investing plan.